Thyrotropin Secreting Adenoma in a Patient with Autoimmune Hypothyroidism: Case Report of a Challenging Diagnosis - E, Sala; G, Carosi; L, Montefusco; E, Ferrante; M, Losa; G, Mantovani; M, Arosio (Archives of Clinical and Medical Case Reports, 2021)
Clinical presentation: We describe a case of a 47-year-old woman with a longtime primary autoimmune hypothyroidism with a progressive rising of TSH levels despite increasing of LT4 therapy. LT4 dose was increased up to 2.9 mcg/kg/day causing an excess of circulating fT4 a minor increase of fT3 concentrations without, however, achieving TSH normalization. The patients was asymptomatic and during the long observation period she had two term pregnancies. A withdrawal of thyroid hormone replacement therapy appropriately induced a further increase of TSH levels and a decrease of fT3 and fT4 below the normal range. LT4 therapy was then resumed and, because TSH levels failed to normalize, central hyperthyroidism or thyroid hormone resistance were suspected. Thyroid levels of first grade relatives were normal, and TSH response to TRH was positive, leaving the diagnosis unclear. The magnetic resonance imaging (MRI) of sellar region revealed a pituitary macroadenoma. The remaining pituitary function was normal. The patient underwent transphenoidal surgery (TNS) and histological examination showed positive immunostaining for TSH, and a mild positivity for GH. After surgery, TSH levels quickly fall down and her replacement therapy could finally be optimized. Conclusions: TSH-secreting pituitary adenomas are rare. Up to now there are few case reports describing their onset in patients with primary hypothyroidism. The coexistence of primary hypothyroidism can make more challenging the diagnosis of TSH-secreting pituitary adenoma.